2017
DOI: 10.1016/j.compositesb.2017.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Concrete cover effect on the bond of GFRP bar and concrete under static loading

Abstract: Paper presents assessment of bond behaviour between GFRP bars and concrete, investigated through set of centric and eccentric pull-out specimens. Main parameters under investigation are 1) bar external surface, 2) concrete mechanical properties and 3) concrete cover. Corresponding tests with steel reinforcement are performed for comparison in some cases. DIC technique was used for recording and evaluating of strain field on frontal side of eccentric specimens. Consequently, cracking patterns and local bond beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(29 citation statements)
references
References 14 publications
3
21
0
5
Order By: Relevance
“…As can be seen in Figure 16, GFRP (type B) bars with 12.7 mm bar diameters showed bond strengths that were 2.3%, 9%, 10.4% and 4.5% lower than those developed by 9.5 mm bar diameters for the embedment lengths of 2.5, 5, 7.5 and 10 times the bar diameter, respectively, with an average reduction of 6.5%. As for 15.9 mm diameters, these percentages were 4.1%, 18.5%, 15.2% and 0.6% less than those developed by 9.5 mm diameters for the same embedment lengths, with an average reduction of 9.6%. For high-strength concrete pullout cubes, it was noticed that a reduction rate in bond strength reduced with increasing the bar diameter for all embedment lengths.…”
Section: Effect Of the Bar Diameter On Bond Strengthmentioning
confidence: 71%
See 1 more Smart Citation
“…As can be seen in Figure 16, GFRP (type B) bars with 12.7 mm bar diameters showed bond strengths that were 2.3%, 9%, 10.4% and 4.5% lower than those developed by 9.5 mm bar diameters for the embedment lengths of 2.5, 5, 7.5 and 10 times the bar diameter, respectively, with an average reduction of 6.5%. As for 15.9 mm diameters, these percentages were 4.1%, 18.5%, 15.2% and 0.6% less than those developed by 9.5 mm diameters for the same embedment lengths, with an average reduction of 9.6%. For high-strength concrete pullout cubes, it was noticed that a reduction rate in bond strength reduced with increasing the bar diameter for all embedment lengths.…”
Section: Effect Of the Bar Diameter On Bond Strengthmentioning
confidence: 71%
“…According to the previous experimental investigations [1,2,4,5,[16][17][18][19][20], it was found that bond strength of GFRP bars in conventional concrete depends on several parameters, such as bar diameter, embedment length, compressive concrete strength, surface configuration, bar type, concrete cover, bar position and transverse reinforcement. Table 1 summarizes the parameters that influence the bond strength considered in the design guidelines (ACI 440.1R [21], CSA-S806 [22], CSA-S6 [23] and JSCE [24]).…”
Section: Introductionmentioning
confidence: 99%
“…Mit der Annahme einer wirklichkeitsnahen Frischbetondruckbeanspruchung können die Schalendicken und damit die Gesamtwandstärke reduziert werden. Dies begünstigt zusätzlich den Einsatz von dauerhaften Bewehrungsmaterialien aus faserverstärkten Kunststoffen , die nur noch sehr geringe Betondeckungen fordern und aufgrund der Korrosionsproblematik von Betonstahl immer mehr an Bedeutung gewinnen.…”
Section: Zusammenfassung Und Ausblickunclassified
“…e bond behavior between FRP bar and ordinary concrete has been widely studied in the literature [8][9][10][11][12][13][14]. A series of pull-out tests were conducted by Hao et al [8] on the effects of rib spacing and rib height of GFRP bar on the bond strength of GFRP bar and ordinary concrete.…”
Section: Introductionmentioning
confidence: 99%